2012
DOI: 10.1007/s10120-012-0203-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of endoscopic submucosal dissection for gastric neoplasm in relationship to endoscopic classification of submucosal fibrosis

Abstract: Background Whether submucosal fibrosis is related to ulceration and affects the outcome of endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) is unknown. This study aimed to determine ESD outcome in relationship to degree of submucosal fibrosis of gastric epithelial neoplasms and to identify factors predictive of submucosal fibrosis. Methods Eight hundred ninety-one patients with 1,027 gastric epithelial neoplasms were treated by ESD from April 2005 to January 2011. Complete en bloc resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 31 publications
(36 reference statements)
1
38
0
1
Order By: Relevance
“…45 A large ESD series has reported SM fibrosis in 20% of the cases with mild F1 and severe F2 in 62% and 38% of those cases, respectively. 29 Similarly, our study revealed SM fibrosis in 24% of the cases with F2 cases accounting for 10 (77%) of the total number of 13 SM fibrosis cases probably due to aggressive or bite-on-bite preoperative biopsy 44 as well as the inclusion of 2 local recurrence cases. Currently, there are no preoperative methods for ascertaining fibrosis, so future studies to establish and evaluate techniques for identifying SM fibrosis would be highly beneficial.…”
Section: Discussionmentioning
confidence: 77%
“…45 A large ESD series has reported SM fibrosis in 20% of the cases with mild F1 and severe F2 in 62% and 38% of those cases, respectively. 29 Similarly, our study revealed SM fibrosis in 24% of the cases with F2 cases accounting for 10 (77%) of the total number of 13 SM fibrosis cases probably due to aggressive or bite-on-bite preoperative biopsy 44 as well as the inclusion of 2 local recurrence cases. Currently, there are no preoperative methods for ascertaining fibrosis, so future studies to establish and evaluate techniques for identifying SM fibrosis would be highly beneficial.…”
Section: Discussionmentioning
confidence: 77%
“…A previous study reported that the presence of ulceration was associated with a long procedure time [7]. The presence of endoscopic ulceration was associated with submucosal fibrosis, and the fibrosis or inflammation caused by ulceration made it more difficult to lift the tumor tissue from the muscle layer, lengthening the procedure time [17,18]. We speculate that PPI administration improved inflammation, made it easier to dissect the submucosa, and thereby shortened the procedure time.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the presence of ulceration was determined only by endoscopic findings without pathologic confirmation. However, concordance between the two methods of identifying ulceration was 99 % in a previous study [17]. Therefore, ulceration can be diagnosed solely on the basis of endoscopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions with < 2.5 mm elevation were classified as flat type scars and those with ≥2.5 mm were protruded type scars. Submucosal fibrosis was defined when no blue transparent layer appears in the submucosal layer and when the submucosal layer could not be easily separated from the whitish muscular area during lesion dissection [7].…”
Section: Definitionmentioning
confidence: 99%